The Influence of the Principal’s Academic Supervision and Teacher Commitment to the Professional Competence of the State Junior High School Teachers - Syafitri, Intan Rahmayuni; Irsyad; Rifma; Yahya (Journal of Education Reseach and Evaluation, 2023)
One of the causes of the low professional competence of a teacher is that the teacher does not prepare learning material properly, does not master learning material, the teacher is less varied in choosing learning methods and models. The main objective of this study is to analyze the commitment of teachers and academic supervisory authorities with regard to the professional competence of teachers in public junior high schools. This study is a national quantitative study with an interdisciplinary focus. This study uses a correlational quantitative approach. The participants in this study were 124 PNS teachers. The instrument used for data collection was a questionnaire prepared using a Likert scale. The correlation formula is used to analyze the research results. The results of the descriptive analysis of teacher professional skills were 80.66%, the principal's academic supervision was 80.79%, and teacher commitment was 80%. The results of the data analysis show that there are significant differences between the professional competence of teachers and the academic dean of the school (58%), between the professional competence of teachers and dean administrators (35.4%), and between the professional competence of teachers and the dean committee (62.8%).